Biological nitrogen removal using combinated fixed-film and suspended reactors by intermittent operation. - Ferrara de Giner, Griselda; Rodríguez Mora, Felipe (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> A biological system was evaluated at laboratory scale, operated by cycles and intermittent in order to remove nitrogen from synthetic wastewater. The system was integrated by two combined bioreactors, the first was used for nitrification (SBBR) and the second for denitrification (SBR). The typical sequence of operation used for both bioreactors was as follows: 15 min for filling up; 270 min for reaction; 45 min for sedimentation; 15 min for discharge, and additionally an aeration-stirring phase of 15 min was included in the second reactor (SBR) before sedimentation. The synthetic wastewater was distributed between both reactors, a fraction (_ = 0,5) was supplied to the SBR to generated enough carbon for the denitrification reaction and the other fraction (1-_) was supplied to the SBBR for the nitrification reaction. The system was operated for 4 cycles/day. The nitrification reached 91% in the SBBR with a surface reaction rate of 12 mg NO3-N/m2.h. The denitrification in the SBR reached 99% with a specific rate of 2.0 mg NO3-N/Kg MLSS.h. The NO3-N and total nitrogen (Nt) concentrations in the effluent were 0.06 and 21.6 mg/L, respectively. The proposed system is efficient for nitrogen removal.